2021
DOI: 10.1182/blood-2021-153653
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toxicity Among Patients with Multiple Myeloma

Abstract: Background: Treatment-related financial burden, or financial toxicity, can detract from mental health and quality of life and can lead patients to alter their care to offset treatment costs. In doing so, these patients compromise adherence which can contribute to disparities (Zafar Oncologist 2013). Among cancers, multiple myeloma treatment is particularly costly due to use of expensive, novel agents, often in combination, and for extended durations. One study found that patients with myeloma frequently report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…1 An increasing amount of attention has been paid to FT in patients with cancer, in large part due to the rising costs of cancer diagnosis and treatment. 2 Previous studies of FT in cancer patients have examined the prevalence of FT among subgroups of patients with different cancer types, 3 , 4 , 5 , 6 cancer stages, 5 , 7 , 8 treatment schemes, 5 , 9 healthcare coverage systems, 10 , 11 , 12 or other subgroups as well as related factors of FT. These studies indicated disparities in prevalence and related factors among subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…1 An increasing amount of attention has been paid to FT in patients with cancer, in large part due to the rising costs of cancer diagnosis and treatment. 2 Previous studies of FT in cancer patients have examined the prevalence of FT among subgroups of patients with different cancer types, 3 , 4 , 5 , 6 cancer stages, 5 , 7 , 8 treatment schemes, 5 , 9 healthcare coverage systems, 10 , 11 , 12 or other subgroups as well as related factors of FT. These studies indicated disparities in prevalence and related factors among subgroups.…”
Section: Introductionmentioning
confidence: 99%